2008
DOI: 10.1124/jpet.108.146514
|View full text |Cite
|
Sign up to set email alerts
|

Old and New Pharmacology: Positive Allosteric Modulation of the α7 Nicotinic Acetylcholine Receptor by the 5-Hydroxytryptamine2B/C Receptor Antagonist SB-206553 (3,5-Dihydro-5-methyl-N-3-pyridinylbenzo[1,2-b:4,5-b′]di pyrrole-1(2H)-carboxamide)

Abstract: The ␣7 nicotinic acetylcholine receptor (nAChR) has been implicated in Alzheimer's disease and schizophrenia, leading to efforts targeted toward discovering agonists and positive allosteric modulators (PAMs) of this receptor. In a Ca 2ϩ flux fluorometric imaging plate reader assay, SB-206553 (3,5-dihydro -5 -methyl -N -3 -pyridinylbenzo [1, 2 -b : 4, 5 -bЈ] -di pyrrole-1(2H)-carboxamide), a compound known as a 5-hydroxytryptamine 2B/2C receptor antagonist, produced an 8-fold potentiation of the evoked calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 27 publications
3
68
0
Order By: Relevance
“…Although PNU-120596 and TQS appear to bind at similar sites in the intrasubunit cavity formed by the four membrane-spanning helices (Young et al, 2008;Gill et al, 2011), there may be alternate protein-PAM interactions, with increased differences in the response to membrane fluidity changes that occur at higher temperature. Although increased temperature had only a modest effect on receptor activation by the allosteric agonist 4-(4-bromophenyl)-3a,4,5,9b-tetrahydro-3H-cyclopenta[c]quinoline-8-sulfonamide (Jindrichova et al, 2012), Sitzia et al, 2011 reported that the potentiating activity of SB-206553, a PAM with properties intermediate to those of the type I and type II PAM classes (Dunlop et al, 2009), was also reduced at 37°C. Although the published data agree that type I PAMs appear to lack in vitro cytotoxicity (at the concentrations of agonists and modulators tested), the data are contradictory regarding the in vitro toxicity of the type II PAM PNU-120596 (Ng et al, 2007;Hu et al, 2009;Dinklo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although PNU-120596 and TQS appear to bind at similar sites in the intrasubunit cavity formed by the four membrane-spanning helices (Young et al, 2008;Gill et al, 2011), there may be alternate protein-PAM interactions, with increased differences in the response to membrane fluidity changes that occur at higher temperature. Although increased temperature had only a modest effect on receptor activation by the allosteric agonist 4-(4-bromophenyl)-3a,4,5,9b-tetrahydro-3H-cyclopenta[c]quinoline-8-sulfonamide (Jindrichova et al, 2012), Sitzia et al, 2011 reported that the potentiating activity of SB-206553, a PAM with properties intermediate to those of the type I and type II PAM classes (Dunlop et al, 2009), was also reduced at 37°C. Although the published data agree that type I PAMs appear to lack in vitro cytotoxicity (at the concentrations of agonists and modulators tested), the data are contradictory regarding the in vitro toxicity of the type II PAM PNU-120596 (Ng et al, 2007;Hu et al, 2009;Dinklo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when analyzed at the molecular level, potentiation is more complex than initially believed. Moreover, PAMs showing macroscopic intermediate type I/II properties were proposed (Dunlop et al, 2009;Malysz et al, 2009;Dinklo et al, 2011;Sahdeo et al, 2014;Chatzidaki and Millar, 2015). Therefore, the classification of type I and type II appears to be an oversimplification resulting mainly from macroscopic observations, and a more thorough classification may be required.…”
Section: Modulatory Sites Pnu-120596mentioning
confidence: 99%
“…Ratiometric determination of intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) in individual HEK293 cells was performed using Fura-2-based microfluorimetry. Methods were similar to those described recently by Dunlop et al (2009). In brief, HEK293 cells were plated on 13-mm round glass coverslips and loaded with Fura-2AM (2 M) by incubation for 30 min at 37°C in a standard HEPESbuffered salt solution (HBSS) supplemented with Pluronic acid 0.02% (w/v).…”
Section: Electrophysiologymentioning
confidence: 99%